Prison and Immigration Industrial Complexes: The Ethnodistillation of People of Color and Immigrants as Economic, Political, and Demographic Threats to US Hegemony - Díaz, Jesse (2012)
Abstract: This paper compares the sociohistorical trends that led to the development of the Prison and Immigration Industrial Complexes by demonstrating their deep roots in American public, racial, political, and penology history, and to show how these industries were used as armaments in the low intensity conflict war to keep blacks "in their place" in the post-Civil Rights Movement era, and now against Latino immigrants in a last ditch effort to preserve a dissipating white hegemonic order as the looming Browning of America unfurls. This study specifically compares the black experience in the Prison Industrial Complex, and how local policies fuel that industry, to the immigrant experience and how the Immigration Industrial Complex lucratively thrives from federal and regional antiimmigrant policies that have fueled its expansion along the border, thereby escalating the "War on Drugs" to the "War on the Border". Scholars have argued that the Prison Industrial Complex ultimately serves to "disappear" people of color from society. I extend that contention to the Immigration Industrial Complex, by arguing that the white ruling class has benefitted the most because countless whites have escaped the wrath of these industries, which is coupled by its motivation to "purify and refine" society, more specifically to "distill" it of the "hypercriminalized" class theoretically composed of people of color in a process previously established as ethnodistillation, which have served to maintain the US' white subjugated social order